Mannose-Modificated Polyethylenimine A Specific and Effective Antibacterial Agent against Escherichia coli - Liu, Mei (Langmuir : the ACS journal of surfaces and colloids, 2018)
Polyethylenimine (PEI) has antimicrobial activity against Gram-positive (Staphylococcus aureus, S. aureus) and Gram-negative (Escherichia coli, E. coli), bacteria but is highly cytotoxic, and the selective antimicrobial activity against S. aureus is obviously better than that against E. coli. To reduce the cytotoxicity and improve the antibacterial activity against E. coli, we modified PEI with d-mannose through nucleophilic addition between primary amine and aldehyde groups to get mannose-modified polyethylenimine copolymer particles (Man-PEI CPs). The use of mannose may provide good targeting ability toward E. coli pili. The antibacterial activity of Man-PEI CPs was investigated. Man-PEI CPs shows specific and very strong killing capability against E. coli at a concentration of 10 μg/mL, which is the highest antimicrobial efficiency compared to that of unmodified PEI (220 μg/mL). The antibacterial mechanism demonstrated that the enhancement in antibacterial activity is due to specific recognition of the mannose and destroying the cell wall of the bacteria by PEIs. Importantly, the Man-PEI CPs show less cytotoxicity and excellent biocompatibility. The results indicate that Man-PEI CPs have great potential as novel antimicrobial materials to prevent bacterial infections and provide specific applications for killing E. coli